2018
DOI: 10.1021/acs.est.8b02667
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Haloarchaea on Speciation of Uranium—A Multispectroscopic Approach

Abstract: Haloarchaea represent a predominant part of the microbial community in rock salt, which can serve as host rock for the disposal of high level radioactive waste. However, knowledge is missing about how Haloarchaea interact with radionuclides. Here, we used a combination of spectroscopic and microscopic methods to study the interactions of an extremely halophilic archaeon with uranium, one of the major radionuclides in high level radioactive waste, on a molecular level. The obtained results show that Halobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Its interactions with this radionuclide have already been investigated by Bader et al . [ 17 19 ]. Both microorganisms differ only in one base pairing of 818 bp of the 16S rRNA gene sequence.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Its interactions with this radionuclide have already been investigated by Bader et al . [ 17 19 ]. Both microorganisms differ only in one base pairing of 818 bp of the 16S rRNA gene sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Afterwards, a slow association occurred, which was only completed after about two weeks. However, at higher uranium(VI) concentrations (85 μM), no desorption phase took place either [ 18 , 19 ]. It can be concluded that microorganisms which belong to the same genus or even species, do not always show the same interaction mechanisms under similar experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations